From transmission to transaction: John Dewey's imaginative vision of teaching. Issue 4 (7th June 2018) - Boyles, Deron
ABSTRACT: This paper uses John Dewey's ([1916]. Democracy and Education . New York: The Free Press) to explore the difference between teaching as transmission and teaching as transaction. Proceeding in three sections, the paper clarifies what Dewey understood to be the problems and promises of teaching, as well as the potential of transactionalism. Experiences from working with teachers in a Dewey-inspired school are included to illustrate the possibilities and limitations of advancing Dewey's imaginative vision.